Effectiveness of Arson Investigation in Barangay 171, North Caloocan; An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Fire can be classified as an accidental or natural occurrence, but if someone deliberately setsfire on someone’s property, it becomes a crime of arson. Arson is a deliberate or willful settingof fire through property and is still a major issue on a global scale, resulting in high costs ofdamage in terms of property loss, injuries, and fatalities. The purpose of this study is to assessthe effectiveness of arson investigation in Barangay 171 North Caloocan.The results of the study about the effectiveness of arson investigation in barangay 171 NorthCaloocan indicate that the effectiveness of arson investigation is based on the sufficientnumbers of arson investigators assigned to arson investigation, which garnered the mostresponse from the respondents with the weighted mean of 3.70 and with the verbalinterpretation of “Strongly Agree”. The researchers suggest measures that can be proposed toaddress the problem encountered.
Keywords: Criminology